If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y + -7 = 25y + 2 Reorder the terms: -7 + 10y = 25y + 2 Reorder the terms: -7 + 10y = 2 + 25y Solving -7 + 10y = 2 + 25y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-25y' to each side of the equation. -7 + 10y + -25y = 2 + 25y + -25y Combine like terms: 10y + -25y = -15y -7 + -15y = 2 + 25y + -25y Combine like terms: 25y + -25y = 0 -7 + -15y = 2 + 0 -7 + -15y = 2 Add '7' to each side of the equation. -7 + 7 + -15y = 2 + 7 Combine like terms: -7 + 7 = 0 0 + -15y = 2 + 7 -15y = 2 + 7 Combine like terms: 2 + 7 = 9 -15y = 9 Divide each side by '-15'. y = -0.6 Simplifying y = -0.6
| 5.92-p=58.63 | | 5-k/7=4 | | -19x-34=56-6 | | 8*0+2y=-16 | | 2(4x+5)=-46+24 | | c+by=a | | 5(4x-9)=220 | | 88=y-2 | | 7x+29=5x+19 | | 86+x=90 | | -76=6x-1 | | 8x-32=24x | | 3x+2y+8=180 | | 8x+2*0=-16 | | -2(x+3)=400 | | 21=s-25 | | 13+d=190 | | 6y+2*0=12 | | -12=2/5z | | -2(b+11)=-26 | | 2(3b+7)=5+6d | | 2p+3-p= | | -11z+5x=18 | | n+-9=-1 | | 5r+6r=12-r | | 6*0+2x=12 | | 5r+6r=12-6 | | 4x+5=8x+30 | | 4w-5-7w= | | 4+3b-3=-17 | | 20x-40=28x | | -6-12n=-282 |